Pollution Characterization, Meteorological Effects, and Sources of Carbon Aerosols in PM2.5 in Urban Xiangtan during Winter - Lizhi He; Zhenghui Xiao; Cheng Xie; Yangfei Ou; Sisi Wang (Aerosol and Air Quality Research)
Abstract Urbanization and industrialization have contributed to increased air pollution in China, yet few studies have focused on carbon aerosols in Xiangtan. To investigate the temporal variations and origins of carbon aerosols in fine particulate matter (PM2.5) in Xiangtan, hourly concentrations of elemental carbon (EC) and organic carbon (OC) were measured from December 2022 to February 2023. The average winter concentrations of OC and EC were 10.75 ± 5.75 µg m–3 and 1.92 ± 0.77 µg m‒3, respectively, which accounted for 16.5% and 3.5% of the total PM2.5, respectively. The winter average ratio of OC/EC was 5.82, and the correlation between EC and OC was weak, indicating that OC and EC originated from many different sources. The winter average level of secondary organic carbon (SOC) was 6.8 ± 5.1 µg m‒3 using the lowest OC/EC value (OC/EC)min, accounting for about 66% of the OC, indicating that SOC is the main source of OC in winter PM2.5 in Xiangtan. The OC level in Xiangtan exhibited clear diurnal variation, which did not coincide with the diurnal variation of OC observed in the metropolis. In contrast, the EC concentration showed relatively flat diurnal variation. Moreover, no uniform weekend patterns were observed for either OC or EC. High concentrations of OC mainly occurred at low and medium temperatures ranging from 7 to 17°C and with relative humidity ranging from 60 to 85%. Additionally, EC and OC concentrations were affected by local pollution sources at low wind speeds. According to potential source contribution function analysis, the EC and OC potential source regions were widely dispersed and the high value source areas of OC and EC were from major traffic cities that were prone to motor vehicle pollution, such as Chang-Zhu-Tan.